2015
DOI: 10.1021/acsnano.5b05999
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Presence Induces Global Immune Changes and Enhances Nanoparticle Clearance

Abstract: Long-circulating nanoparticles are essential for increasing tumor accumulation to provide therapeutic efficacy. While it is known that tumor presence can alter the immune system, very few studies have explored this impact on nanoparticle circulation. In this report, we demonstrate how the presence of a tumor can change the local and global immune system, which dramatically increases particle clearance. We found that tumor presence significantly increased clearance of PRINT hydrogel nanoparticles from the circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 53 publications
5
42
0
Order By: Relevance
“…enhance understanding of nanoparticle performance in animal models (24)(25)(26)(27), strategies to normalize tumor vasculature (28), systematic investigations into ideal nanoparticle characteristics (24,29), and a focus on smaller (20-30-nm-sized) nanocarriers (24,30,31). Despite the promise of these approaches, the diversity of human cancers necessitates equivalently diverse delivery approaches (23,32) and opportunity for improvement remains, particularly in the area of enhancing uniformity of tumor distribution.…”
mentioning
confidence: 99%
“…enhance understanding of nanoparticle performance in animal models (24)(25)(26)(27), strategies to normalize tumor vasculature (28), systematic investigations into ideal nanoparticle characteristics (24,29), and a focus on smaller (20-30-nm-sized) nanocarriers (24,30,31). Despite the promise of these approaches, the diversity of human cancers necessitates equivalently diverse delivery approaches (23,32) and opportunity for improvement remains, particularly in the area of enhancing uniformity of tumor distribution.…”
mentioning
confidence: 99%
“…On this account, it was vital to identify, which components are potentially released from the 3D-printed parts during application and contribute to the observed cytotoxicity. While TPO-acting as a photo-absorber-was present in all our resins, previous studies on the usage of TPO or its derivative (ethyl 2,4,6-trimethylbenzoylphenylphosphinate) to establish artificial extracellular environments showed that TPO can be safely used and should not influence cell viability, even when used at concentrations as high as 2% w/w compared to concentrations ranging from 0.1% to 0.25% in our resins [26,27]. Uncured resin, as another source for the observed cytotoxicity, should have been consumed in the post-curing process, where 3D-printed objects were exposed to UV-light to achieve complete conversion, and in the sterilization process, which also involved UV-light.…”
Section: Cytotoxic Effect On Human Umbilical Vein Endothelial Cells (mentioning
confidence: 81%
“…However, the obtained data were controversial and even conflictive, which is understandable as the biological behavior of nanodelivery systems can be affected by a number of parameters such as chemical structure, shape, potential, and size of the nanoparticles . On the other hand, the varied biological models used in different studies may also interfere with the in vitro and in vivo research findings …”
Section: Resultsmentioning
confidence: 99%